Differential effects of neuropsychiatric symptoms and social support in mild cognitive impairment participants - Sng, Hui Xin (Nanyang Technological University, 2020)
Recent decades of research pointed out 3 significant paradigm shifts, namely a shift of focus to the period prior to Alzheimer’s Disease diagnosis, increasing significance of neuropsychiatric symptoms (NPS), and changing to a biopsychosocial approach to Alzheimer’s Disease. Thus, this study cross-sectionally examines the interaction of baseline NPS and social support (i.e., residing with a co-participant) for mild cognitive impairment (MCI) participants in predicting for baseline cognition levels and cortical thickness, and pathology at death. Participants were from the National Alzheimer’s Coordinating Centre with a Clinical Dementia Rating score of 0.5 (MCI) and data were collected via neuropsychological battery tests, magnetic resonance imaging scans, and Braak staging as well as Consortium to Establish a Registry for Alzheimer’s Disease scoring. Neuropsychiatric symptoms (occurrence and severity) and social support were hypothesised to interact and predict higher cognition levels, increased cortical thickness and lower amyloid and tau pathology. Multiple linear regression analysis was carried out among 8,509 participants for cognition levels, as well as further sub-group analysis for cortical thickness and pathology. Significant moderation effects of social support were found on the relationship between NPS and both cognition levels (NPS severity) and pathology at death (NPS severity and occurrence). Call frequency was likewise found to moderate the relationship between NPS and pathology. No significant interaction effects were found between social support and NPS to predict cortical thickness. This study highlighted the beneficial and protective effects of social support and its significance particularly to individuals with NPS even at the MCI stage.